Echocardiography and Pulmonary Arterial Hypertension - Eduardo Bossone; Rodolfo Citro; Alberto Ruggiero; Bettina Kuersten; Giovanni Gregorio; Francesco Blasi; Luigi Allegra (Monaldi Archives for Chest Disease, 2016)
Pulmonary Arterial Hypertension (PAH) is an heterogeneous condition brought on by a wide range of causes. It is characterized by structural changes in small pulmonary arteries, that produce a progressive increase in pulmonary artery pressure and pulmonary vascular resistance, ultimately leading to right ventricle failure and death. Given the non-specific nature of its early symptoms and signs, PAH is often diagnosed in its advanced stages. Along with a careful clinical assessment and an accurate electrocardiogram/Chest X-ray interpretation, echocardiography is an essential test in the evaluation of patient with PAH. In fact it not only provides an accurate estimate of pulmonary pressure at rest and during exercise, but may also help to exclude any secondary causes, predict the prognosis, monitor the efficacy of specific therapeutic interventions and detect the preclinical stage of the disease.